2014
DOI: 10.1111/jocn.12593
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of nurse consultants in England to the public health leadership agenda

Abstract: This research contributes to the global discussion currently being held about the nomenclature of advanced nurse practitioner roles, their scope and influence. The challenge for nurses to contribute meaningfully to public health structures at an advanced level is a concern for all nations seeking the common goal of addressing public health needs within their populations and suggests that further development of our understanding of the potential contribution of advanced nurses is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…[414243] Franks also reported that the development of this role occurs not only through clinical needs but also through political motives such as the need for the development of nursing roles and economic change. [17] Therefore, these results are consistent with our results that demonstrate the necessity of support of nurse consultants and introducing it to organizations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[414243] Franks also reported that the development of this role occurs not only through clinical needs but also through political motives such as the need for the development of nursing roles and economic change. [17] Therefore, these results are consistent with our results that demonstrate the necessity of support of nurse consultants and introducing it to organizations.…”
Section: Discussionsupporting
confidence: 92%
“…[1516] On the other hand, this role has a great impact on the health promotion of chronic patients. [121718] The results of nursing consultation include improving quality of life, satisfaction, awareness, and adherence in patients; preventing and reducing distress, stress, anxiety, and complications; reducing costs and readmission; and also preventing worsening of the disease and mortality. [1219202122] Unfortunately, in Iran, patients do not receive nursing consultation services and this role does not have a real status.…”
Section: Introductionmentioning
confidence: 99%
“…This is demonstrated, for instance, by the expansion of the number of nurse practitioners in North America [1]. Furthermore, nurses have assumed leadership roles [12] and have taken over duties traditionally performed by physicians [2,6]. One such role is the triaging of outpatient referrals in healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly two decades later, it seems the number of NC roles created is lower than envisaged, a recent cancer nurse workforce survey in England indicating less than 1% of nurses specializing in cancer are working in NC roles (47 WTE posts) (Macmillan Cancer Support, ). This suggests that decision‐makers underappreciate the value and worth of these roles (Franks, ). Yet England's Cancer Workforce Plan (Health Education England, ) highlights the need for a specialist cancer workforce in supporting the rising numbers of people now surviving cancer.…”
Section: Introductionmentioning
confidence: 99%